Tadalafil has biologic activity in human melanoma: results of a pilot trial with Tadalafil in patients with metastatic Melanoma (TaMe) - Hassel, Jessica C.; Bender, Carolin; Winkler, Julia K.; Halama, Niels; Dimitrakopoulou-Strauss, Antonia; Haefeli, Walter E.; Jäger, Dirk; Enk, Alexander; Utikal, Jochen; Umansky, Viktor (OncoImmunology, 2017)
Myeloid-derived suppressor cells (MDSCs) are known to play a critical role in the suppression of T cell antitumor responses. Our preclinical data showed that the phosphodiesterase (PDE)-5 inhibitor sildenafil impaired MDSC functions, enhanced intratumoral T cell activity and prolonged survival of melanoma-bearing mice. In this study, we evaluated biologic effects, safety and efficacy of palliative treatment with the PDE-5 inhibitor tadalafil in metastatic melanoma patients. We conducted an open-label, dose de-escalation trial with tadalafil in pretreated metastatic melanoma patients. Tumor and peripheral blood samples were taken before and 4 weeks after the start of treatment. Samples were investigated by immunohistochemistry and FACS analysis, for different immune subsets with numbers of CD8+ tumor-infiltrating lymphocytes (TIL) as primary end point. Stable disease was achieved in 3/12 patients (25%). Median progression-free survival was 4.6 mo (range 0.7-7.1), median overall survival (OS) 8.5 mo (range 2.7-23.7). The treatment was well tolerated. Stable patients displayed significantly higher numbers of CD8+ TIL in the center of metastases before treatment as compared with progressive patients. Upon the therapy, they showed increased expression of ζ-chain (used as a marker of T cell activation) in CD8+ and CD4+TILs and CD8+T cells in the peripheral blood as compared with baseline. Our study suggests that the PDE-5 inhibitor tadalafil can improve clinical outcome of advanced melanoma patients by enhancing antitumor immunity and highlights its potential application in combined melanoma immunotherapy.